تصميم وحدات دراسية لمقرر النحو لطلبة معهد تعليم اللغة العربية بالجامعة ‏الإسلامية بالمدينة المنورة: برنامج مقترح : - صاعدي، ماهر بن دخيل الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
There are certain deficiencies in the syllabus of teaching the Arabic language used by the Institute of Teaching Arabic to Non-Native Speakers at Islamic University of Medina. These deficiencies have led the syllabus to fail to take into account the non-native Arabic learners' needs. The goals of the language teaching textbooks used at the institute have failed to take into account that learners should directly use the knowledge they learned from the textbooks in their communication to practice spoken and written expressions. Additionally, the content of these textbooks have failed to keep up with the changes that have occurred in the teaching and learning process. Also, these textbooks do not meet the standards of a good textbook as well as the linguistic and educational quality standards. This study aims to design educational units of Arabic grammar for the learners of Arabic at the Islamic University of Medina. In order to design these proposed educational units, the study identifies the requirements for designing Arabic grammar modules for non-Arabic speakers, recognizes the deficiencies in teaching Arabic grammar at the Institute of Teaching Arabic to Non-Native Speakers at Islamic University of Medina, and analyzes the students' needs to learn Arabic grammar at the institute as well. The current study uses the descriptive deductive approach to collect the theoretical material and identify students' needs. The analytic approach is used to analyze the questionnaires and identify the students' needs. The questionnaire was analyzed using SPSS. The results of the analysis show that the curriculum does not meet the needs of students learning and it lacks many of the components that must be available in the curricula of teaching Arabic to non-native speakers. Accordingly, the present study has designed these proposed educational units of Arabic grammar with a guide for teachers that can help them teach these units. In addition, this study will help students in the institute to learn the grammar according to their needs. Finally, the present study proposes a set of recommendations and proposals in light of the results.